STUDI KOMPARATIF SELF REGULATED LEARNING SISWA ASRAMA DAN NON-ASRAMA DI SMA IT IZZUDDIN PALEMBANG - Bagus Pamungkas; Fajri Ismail; Baldi Anggara (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2020)
In IT Izzuddin High School Palembang, after the learning activities are finished students/students have a different environment. Consists of boarding students and non-boarding students. The existence of environmental differences will certainly provide different support and obstacles. Starting from this the researcher wants to compare the self-regulated learning of boarding and non-boarding students with the title “Comparative Study of Self Regulated Learning of Dormitory and Non-Boarding Students at IT Izzuddin Palembang High School”. This study aims to determine whether there are differences in self-regulated learning between boarding students and non-boarding students at IT Izzuddin Palembang High School.This research method uses a quantitative approach. This type of research is comparative research. The population in this study were all students of IT Izzuddin Palembang High School it the 2019/2020 school years, totaling 140 students, consisting of 69 boarding students and 71 non-boarding students. From this population, a sample of 60 boarding students and 63 non-boarding students was taken. The sampling technique is proportionate stratified random sampling. After the content validity test, Cronbach's alpha coefficient of 0.730 was obtained. The result is > 0.6 then the instrument is reliable. Methods of data analysis using t-test and then given an interpretation of the results.Based on the results og the hypothesis test, t = 2.777 with p = 0.006. Because the value of p < 5% (0.006 < 0.05) then H0 is rejected and H1 is accepted, there is a significant difference in self-regulated learning between boarding and non-boarding students at IT Izzuddin Palembang High School where the level of self-regulated learning of boarding students is higher compared to no